Development and implementation of computer integrated production planning system for job shop company - Mat Saman, Muhamad Zameri (Faculty of Mechanical Engineering, 1999)
Since the introduction of the computer in the manufacturing floor, the competitiveness of the manufcturing industry has increased tremendously. Manufacturers have implemented many software packages in order to cope with the ever-challenging production world. Industries claimed difficulties in implementing the general-purpose computerized production planning system, such as MRP-II. aThis is due to too many parameters that have to be defined in the system [5, 7]. Thus, the main objective of using computerized system in production planning could not be achieved. The aim of this study is to help the job shop company in improving the effectiveness of the production plan and specifically to develop a computerized production planning system for a metal stamping company. After the weaknesses and main problems of the current production planning system have been identified, a computer system will be developed in order to improve the feasibility and effectiveness of the production plan.